Gender and mobility planning: The influence of national culture on planning processes. Issue 2 (June 2022) - Porrazzo, Alexandra; Samson, Caroline; Freudendal-Pedersen, Malene
Highlights: National culture impacts how mobility planners consider gender in planning processes. By planning for everybody, Copenhagen mobility planners obscure gendered differences. Societal avoidance of feminist topics affects mobility planning. Blind acceptance of equality is a barrier to gender sensitive mobility planning. Abstract: Gender sensitive planning processes have been increasingly hailed as necessary for the optimization of sustainable mobility systems. Moreover, a plethora of recommendations, guidelines, and policy plans exist for integrating gender sensitivity into policy and practice. This article considers Copenhagen (Denmark) as a critical case, and uses a qualitative analysis to understand the cultural reasons for why this best-practice is not being adopted. In order to do so, the term 'cultural black boxing' is developed by merging knowledge from science and technology studies and feminist theories. Copenhagen mobility planners are interviewed, and the analysis shows that mobility planners center themselves around equality, not equity, and distance themselves from discussing gender inequality. Furthermore, mobility planning reacts to already made visible groups and focuses on narratives of existing equality, not persisting inequality. In this way, cultural black boxing is found to both occur in the way mobility planners are formed by their national identity, and in the way their planning processes are subsequently influenced.